A case of squamous cell carcinoma arising from a suprapubic cystostomy tract in a patient with spinal bifida: Immunohistochemical analysis and literature review. Issue 1 (8th November 2022) - Sawazaki, Harutake; Kitamura, Yosuke; Asano, Atsushi; Ito, Yuji; Tsuda, Hitoshi
Abstract : Introduction: Squamous cell carcinoma arising from a suprapubic cystostomy tract is a rare complication of an indwelling catheter and is caused by long‐term inflammation and mechanical irritation. Prognosis is relatively poor. Biomarkers in the cancer pathway have not been investigated. Case presentation: A 61‐year‐old woman with a 34‐year history of suprapubic catheter placement presented with a rapidly growing elevated lesion around the cystostomy site. Tumor biopsy confirmed squamous cell carcinoma. Local excision with partial cystectomy was performed. Multiple metastases were identified 5 months later. The patient died 14 months after the initial treatment. Immunohistochemical analysis of the resected specimen revealed alterations in vascular endothelial growth factor, epidermal growth factor receptor, cyclooxygenase‐2, and Ki‐67. Conclusion: We encountered a case of squamous cell carcinoma arising from a suprapubic cystostomy tract. Immunohistochemical analysis revealed activation of multiple carcinogenic pathways in cancer cells, including those for angiogenesis, signal transduction by epidermal growth factor receptor, inflammation, and cell proliferation.